Micro-Mobilities in Lockdown. Issue 1 (1st March 2020) - Merriman, Peter
Abstract: In this paper I reflect upon my own micro-mobilities and embodied mobile practices living and working under COVID-19 government restrictions in Wales in mid-2020. I use the opportunity to reflect upon the past ten years of Transfers and to think about future research in the field of mobility studies, arguing that an attention to seemingly ordinary embodied movements and mobilities provides one avenue by which mobility scholars could move beyond the mobility/immobility binary and approach mobility as being more than transport, migration, and communication. Mobility is, I suggest, ubiquitous—even during government lockdowns—and I explain how Deleuze and Guattari's concepts of the "molar" and "molecular" can be useful for understanding how some movements become perceptible and others imperceptible, and why scholars frequently draw a clear distinction between mobility and immobility.